Techno-economic analysis for the production of acrylonitrile, propylene or isosorbide in a sugarcane biorefinery annexed to a typical South African sugar mill - Rode, Lukhanyo (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024